Influence Of Market Traders Cooperatives (KOPPAS) On Capital Of Traders On The North Cipete Market - Hasanah HASANAH (International Journal of Environmental, Sustainability, and Social Science, 2022)
Cooperatives are associations of people who have the same goal, namely to improve the standard of living and improve the welfare of their members because, in general, cooperative members are people who have a weak economic level. One type of cooperative is the Pasar Merchant Cooperative (KOPPAS), which is a type of cooperative whose members consist of traditional markets traders who want to develop their business. The purpose of the study was to determine the effect of KOPPAS on the Capital of North Cipete Traditional markets Traders. The research method used in this study; the author uses associative research to find the relationship between two variables, namely the variables X (KOPPAS), and Y (Capital). And it is a survey because the research is conducted by visiting the object of research, and case studies are conducted to clarify the problem in the research. The data sources used are primary data sources and secondary data sources. The samples taken were 96 traders as respondents. The results obtained are that there is a significant influence between traditional markets traders' cooperatives on traditional markets traders' capital, as well as the reasons for being an inactive member, namely, there is no time to go to the cooperative, there are other lenders that are easier to borrow, traders can borrow funds should not be large, the loan repayment period is short.